Protecting Older People from Burglary: Prevalence of Security Devices in the Home of Older Adults in Perth, Western Australia - Lee, Hoe; Lee, Andy; Clinton, M.; Zhang, Guicheng; Fraser, Michelle (Hawworth Press, Inc, 2008)
Fear restricts the activity of older adults, potentially leading to social isolation and unhealthy life styles. Consequently, this population remains a priority for home security research and intervention. One option is to increase home security by installing security devices. However, little is known about how older adults protect their homes. In this study, 5,582 community-dwelling older people completed a cross-sectional survey. The survey was able to document the prevalence of security measures taken by older adults. More than 70% of the respondents had security screens and key-operated deadlocks and 148 (2.7%) respondents reported no security features. Respondents living alone had the lowest prevalence of home security devices. Female living alone protected their home differently from male living alone by installing different security devices. Logistic regression analysis indicated that older adults living in detached houses feel particularly vulnerable to burglary (p < .001). These survey findings have practical implication for burglary prevention.